Hambatan Guru-Guru dalam Pembelajaran Daring di SMA Se-Kecamatan Bukit Raya Pekanbaru - Ratna Sari, Dian; Nazirun, Nazirun (UIR Press, 2023)
Since 2019, the world has been faced with a problem, namely the Covid-19 pandemic. So that schools are experiencing obstacles, namely obstacles for teachers in online learning at High Schools (SMA) in Bukit Raya District. Where as a start to start the research process, interviews were conducted with Indonesian language teachers to obtain information on how the implementation of online learning was held in high schools throughout Bukit Raya District, Pekanbaru City. The method used in this thesis is a quantitative method. The population in this study were Indonesian language teachers at SMAs in Bukit Raya Pekanbaru District. The theory used is the theory of E- Learning. The results of this study indicate that the implementation of online learning at SMA Se, Bukit Raya District, is not running effectively due to inadequate internet network limitations. The proof of the hypothesis in this thesis is in the results of the questionnaire questions to teachers who experience obstacles in terms of science and technology indicators as much as 99.98%, teacher obstacles in the internet network indicator as much as 99.94%, teacher obstacles in indicators of supporting factors as much as 99.96%, teacher's obstacles in terms of facilities and infrastructure indicators as much as 99.96%, teacher's obstacles in terms of facilities and infrastructure indicators as much as 103, 67%, teacher's obstacles in terms of funds or budget indicators as much as 99 .9%, teacher constraints on inhibiting factor indicators 99.8%.